Structural Adjustment and Forest Resources : The Impact of World Bank Operations - Pandey, Kiran D.; Wheeler, David (World Bank, Washington, DC, 2014)
Over two decades, the World Bank has undertaken many structural adjustment operations with governments of developing countries. During negotiations for structural adjustment loans (SALs), partner governments agree to specific policy reforms, whose implementation becomes a condition for disbursement of SAL funds. Conditionality varies with local circumstances, but generally supports privatization of state enterprises, liberalization of the domestic economy, and openness in international trade. Structural adjustment operations have often been controversial because they are explicitly political. Opposition, or support reflects ideological perspectives, perceptions of who gains, and who loses economically from a SAL, or beliefs about its environmental, and social impacts. Environmental groups express particular concern about SALs' impacts on the rate of deforestation. Debate about adjustment, and deforestation has been fueled largely by anecdotes, and a few country cases bases on limited time-series data. The authors broaden the analysis by combining a complete record of Bank SAL operations, with a 38-year socioeconomic database for 112 developing countries. They find that adjustment has greatly affected imports, exports, consumption, and production in many forest products sectors (such as fuel-wood, sawn-wood, panels, pulp, and paper). Some activities have increased, and some declined, but overall, the effects have balanced each other. The net impact on domestic round-wood production, the authors' proxy for forest exploitation, has been almost exactly zero. Their results suggest that growth in round-wood production is explained well by population growth, urbanization, and world demand for forest products. Their findings suggest that adjustment has not promoted domestic deforestation, but it has increased net imports of wood products, implying some displacement of pressure onto other countries' forest resources. They also find that devaluations have significantly increased the exploitation of forest resources.